Genome sequencing of Inonotus obliquus reveals insights into candidate genes involved in secondary metabolite biosynthesis - Yingce Duan; Haiyan Han; Jianzhao Qi; Jin-ming Gao; Zhichao Xu; Pengchao Wang; Jie Zhang; Chengwei Liu (BMC Genomics, 2022)
Abstract Background Inonotus obliquus is an important edible and medicinal mushroom that was shown to have many pharmacological activities in preclinical trials, including anti-inflammatory, antitumor, immunomodulatory, and antioxidant effects. However, the biosynthesis of these pharmacological components has rarely been reported. The lack of genomic information has hindered further molecular characterization of this mushroom. Results In this study, we report the genome of I. obliquus using a combined high-throughput Illumina NovaSeq with Oxford Nanopore PromethION sequencing platform. The de novo assembled 38.18 Mb I. obliquus genome was determined to harbor 12,525 predicted protein-coding genes, with 81.83% of them having detectable sequence similarities to others available in public databases. Phylogenetic analysis revealed the close evolutionary relationship of I. obliquus with Fomitiporia mediterranea and Sanghuangporus baumii in the Hymenochaetales clade. According to the distribution of reproduction-related genes, we predict that this mushroom possesses a tetrapolar heterothallic reproductive system. The I. obliquus genome was found to encode a repertoire of enzymes involved in carbohydrate metabolism, along with 135 cytochrome P450 proteins. The genome annotation revealed genes encoding key enzymes responsible for secondary metabolite biosynthesis, such as polysaccharides, polyketides, and terpenoids. Among them, we found four polyketide synthases and 20 sesquiterpenoid synthases belonging to four more types of cyclization mechanism, as well as 13 putative biosynthesis gene clusters involved in terpenoid synthesis in I. obliquus. Conclusions To the best of our knowledge, this is the first reported genome of I. obliquus; we discussed its genome characteristics and functional annotations in detail and predicted secondary metabolic biosynthesis-related genes, which provides genomic information for future studies on its associated molecular mechanism.